Profile of Entrepreneurial Interests of Science Teacher Candidates - Yamin, M.; Imran, Ali; Muliadi, Agus (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to describing biology students’ perceptions of entrepreneurial interest. This study is an exploratory research with 55 biology education students as respondents. The research instrument used was a closed questionnaire with degraded answers according to a Likert scale that had been validated by experts and declared valid. Analysis of research data used is descriptive quantitative statistics and inferential statistics with Anova test at a significance level of 5%. The results of the study show that (1) the perceptions of biology education students regarding entrepreneurial interest are as follows: second-semester students have an average score of 3.05 with a category of Tall, fourth-semester students have an average score of 3.01 with a category of Tall, sixth-semester students have an average score of 3.23 with a category of Tall, and eighth-semester students have an average score of 3.00 with a category of Tall; (2) no significant difference in the perceptions of second, fourth, sixth, and eighth-semester students regarding entrepreneurial interest, which is proven by a significance value of 0.554, which is greater than 0.05 (>0.05).